2022
DOI: 10.1002/gj.4575
|View full text |Cite
|
Sign up to set email alerts
|

The floating astronomical time scale for the terrestrial Early Permian Fengcheng Formation from the Junggar Basin and its stratigraphic and palaeoclimate implications

Abstract: The Permian Fengcheng Formation of the Mahu Sag in the Jungar Basin is one of the most important hydrocarbon source rocks in Xinjiang oil field. The preservation of the geological records of Milankovitch cycles can be studied to understand the history of the Earth's evolution and sedimentary processes, and high-resolution astronomical time scales (ATS) can be obtained by analysing (quasi) periodic sedimentary signals in geological records. In this study, the natural gamma ray (GR) and density (DEN) logging dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Located in northwestern China (~45 °N, 85 °E), the Junggar Basin is a huge inland lake basin that is tectonically constricted by the Hala'alate and Zhayier Mountains to the northwest, the Kelamaili Mountains to the northeast, and the Bogda Mountains to the south (Figures 1A, B). Within the Junggar Basin, an approximately 1.5km-thick stratigraphic sequence adequately documents important long-term features of the tectonic evolution of Central Asia, in addition to the evolution of paleoclimate and paleoenvironmental conditions of the continental region at middle to high latitudes in the Northern Hemisphere from the Paleozoic to the Cenozoic (Huang et al, 2021;Tang et al, 2022). With its location in the northwestern part of the Junggar Basin, the Mahu Sag is a major oil-bearing depression of approximately 5,000 km 2 in area (Yu et al, 2018b).…”
Section: Geological Settingmentioning
confidence: 77%
See 4 more Smart Citations
“…Located in northwestern China (~45 °N, 85 °E), the Junggar Basin is a huge inland lake basin that is tectonically constricted by the Hala'alate and Zhayier Mountains to the northwest, the Kelamaili Mountains to the northeast, and the Bogda Mountains to the south (Figures 1A, B). Within the Junggar Basin, an approximately 1.5km-thick stratigraphic sequence adequately documents important long-term features of the tectonic evolution of Central Asia, in addition to the evolution of paleoclimate and paleoenvironmental conditions of the continental region at middle to high latitudes in the Northern Hemisphere from the Paleozoic to the Cenozoic (Huang et al, 2021;Tang et al, 2022). With its location in the northwestern part of the Junggar Basin, the Mahu Sag is a major oil-bearing depression of approximately 5,000 km 2 in area (Yu et al, 2018b).…”
Section: Geological Settingmentioning
confidence: 77%
“…Using null hypothesis significance levels < 0.01, the most prominent peaks occurring at 9.3 and 17 cm/kyr represent the most likely sedimentation rates in MY-1 well (Figure 4A). Previous cyclostratigraphic analyses using density logging data indicated that the average deposition rate of the P 1 f 1 and P 1 f 2 members of the Fengcheng Formation was approximately 9 cm/kyr (e.g., Tang et al, 2022). We therefore preferred the 9.3 cm/kyr peak as the optimal rate of sedimentation.…”
Section: Cycles In the Stratigraphic Domainmentioning
confidence: 94%
See 3 more Smart Citations